Online Hate and its Routes to Aggression: A Research Agenda - George, Joey (2021)
The Internet has provided human civilization hitherto unimaginable tools with which to connect, communicate and coexist. Unfortunately, those same tools are being viciously maneuvered to spread ethno-racial and religious hatred and romanticize violence, where mass shooters are canonized as saints. The internet is now replete with vituperative chat rooms, web pages, discussion boards, forums, videos, music, and games that denigrate and bully marginalized outgroups either blatantly or through innuendoes. To that extent, it is almost impossible now to navigate through the internet without encountering hateful ideologies and propaganda that deepen societal fissures and instigate violence. Though journalism has put the spotlight on the link between online radicalization and real-world hate crimes, it is still an open empirical question. The existing evidence has been merely anecdotal interspersed with theoretical speculation and data driven empiricism cutting across scientific disciplines. This paper lays out a research agenda that may shed more light on this causal link between online hate and hate crimes